1989
DOI: 10.1111/j.1526-4610.1989.hed2908498.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in PGE2 and TXA2 in the Saliva of Common Migraine Patients. Action of Calcium Channel Blockers

Abstract: PGE2 and TXA2 levels and their modulation by nicardipine, a calcium blocking agent, have been studied in patients suffering from migraine. The levels of both metabolites were determined in saliva obtained during the migraine attacks, during the intervals between attacks, and after 2 months of treatment with nicardipine (20 mg every 8 h.) or placebo. The therapeutic response was evaluated on the basis of the number of migraine attacks. The results show a significant increase in the levels of both eicosanoids du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 23 publications
1
21
1
2
Order By: Relevance
“…Along with other research, this may indicate that each migraine attack serves to reset the system with regard to the activation, which has been built up during the headache‐free interval, meaning that migraine is subject to cyclicity 29,30 . Thus, in accordance with previous work on inflammatory mediators in the periphery, the present data may indicate that migraine is a process localized to the central nervous system 10‐12 . However, future studies are needed to investigate whether the peripheral level of inflammatory mediators could be an indicator of an impending migraine attack.…”
Section: Commentssupporting
confidence: 88%
See 1 more Smart Citation
“…Along with other research, this may indicate that each migraine attack serves to reset the system with regard to the activation, which has been built up during the headache‐free interval, meaning that migraine is subject to cyclicity 29,30 . Thus, in accordance with previous work on inflammatory mediators in the periphery, the present data may indicate that migraine is a process localized to the central nervous system 10‐12 . However, future studies are needed to investigate whether the peripheral level of inflammatory mediators could be an indicator of an impending migraine attack.…”
Section: Commentssupporting
confidence: 88%
“…It has been shown that leukotriene plasma levels are increased during migraine attacks 10 . Tuca and coworkers also found that PGE 2 and thromboxane A 2 (TXA 2 ) levels were increased in saliva during migraine attacks 11 . Comparable to these results, another study showed a significant increase in PGE 2 plasma levels during the attack; in a headache‐free interval, PGE 2 levels were reported to be lower in patients with migraine compared with a control group 12 .…”
mentioning
confidence: 93%
“…We recently reported that the combination of increasing dietary n- 3 fatty acids with concurrent reduction in n-6 LA produced statistically significant, clinically relevant improvements in headache frequency, intensity and quality of life in chronic headache patients [24], a condition with reported elevations of AA-derived mediators in blood and saliva [25, 24, 26]. Blood collected from this trial provides a unique opportunity to evaluate the effects of targeted alterations of dietary n-3 and n-6 fatty acids on plasma esterified and unesterified fatty acid concentrations [19, 24], which could be used as biomarkers to relate efficacy in dietary treatment effects.…”
Section: Introductionmentioning
confidence: 99%
“…During myocardial infarction and angina, plasma concentrations of thromboxane and histamine are increased (29,31). Thromboxane concentration has also been reported to increase during migraine attacks (32). Thus these endogenous ligands may act in concert to augment vasoconstrictor effects of sumatriptan, especially under conditions of vascular injury.…”
mentioning
confidence: 99%